Retinal vascular alterations as assessment indicators of atherosclerotic cardiovascular disease risk in dyslipidemia patients - He, Yu; Wang, Guo-hong; Qin, Ming-zhao; Cao, Kai; Zhang, Yong-peng; Jiao, Xuan; Zhang, Zheng; Liu, Qi; Liu, Qian; Ma, Jin-bao (Frontiers in Cardiovascular Medicine, 2025)
IntroductionAtherosclerotic cardiovascular disease (ASCVD) remains the leading cause of global mortality, particularly among individuals with dyslipidemia. Traditionally, the retina has been considered a key site for examining microvascular changes. Recent evidence, however, indicates that retinal alterations may also reflect macrovascular changes. This study proposes a hypothesis in which Optical Coherence Tomography Angiography (OCTA) is utilized to evaluate retinal vascular changes as a potential biomarker for ASCVD risk assessment in dyslipidemia patients.MethodsIn this cross-sectional study, 261 dyslipidemia patients were recruited and classified into non-ASCVD and ASCVD groups. OCTA was performed on all patients, with the macula and optic disc being the primary areas of assessment. The following parameters were measured: retinal vessel density (VD), retinal nerve fiber layer (RNFL) thickness, retinal thickness, foveal avascular zone (FAZ) area, FAZ perimeter, and VD within a 300 μm width ring surrounding the FAZ (FD). Ultimately, data from 231 eyes were analyzed. Comparisons of OCTA-derived metrics between groups were made, and receiver operating characteristic (ROC) curve analysis was conducted to assess the discriminatory power of these metrics for identifying ASCVD in dyslipidemia patients. The DeLong test was used to compare areas under the ROC curve for these indicators. All statistical tests were two-tailed, with significance set at P < 0.05.ResultsIn the ASCVD group, RNFL thickness, superficial capillary plexus (SCP) parafoveal VD, SCP perifoveal VD, macular parafoveal thickness, and FD were significantly lower compared to the non-ASCVD group. ROC curve analysis confirmed the predictive value of these indicators for ASCVD identification in dyslipidemia patients. SCP parafoveal VD, SCP perifoveal VD, and FD correspond to the macular superficial capillary plexus vessel densities. When combined, these indicators formed a new composite measure, macular superficial vessel density (MSVD). The ROC curve further validated MSVD's predictive utility for ASCVD in dyslipidemia patients, with the optimal threshold identified at 143.22% using the Youden index.ConclusionsOCTA-derived indicators, particularly MSVD, demonstrate significant potential as novel biomarkers for ASCVD risk assessment in dyslipidemia patients.